An observational study examining the relationship between respiratory symptoms, airway inflammation and bacteriology in children with severe neurodisability. - Ruth E Trinick; Lara Bunni; Kent Thorburn; Angela P Hackett; Mark Dalzell; Paul S McNamara (PLoS ONE, 2015)
Background Children with severe neurodisability (ND) commonly suffer from chronic respiratory symptoms that impact greatly on quality of life, and lead to recurrent hospital admissions. This morbidity (and its causes) is poorly described, despite being well recognised by paediatricians. In this study, we characterised respiratory symptoms in children with ND at times of stability and deterioration. We also assessed the relationship between respiratory symptoms, lower airway inflammatory markers and levels of infection/colonisation. Methods ND children were recruited upon admission for elective surgery (Elective-ND [n = 16]), or acutely upon admission to Intensive Care (PICU-ND [n = 19]), and compared to healthy control children [n = 12]. Parents completed a validated respiratory symptom questionnaire in which symptoms associated with activity were removed (total maximal score of 108). Bronchoalveolar lavage (BAL) was collected, and BAL neutrophil counts, IL-8 and TGFβ-1 levels measured. BAL microbial analysis was performed using a 16S/18S rRNA gene based assay and Pseudomonas aeruginosa PCR. Results All ND children had high levels of respiratory symptoms (median [IQR] symptom score PICU-ND, 55[38-64]; Elective-ND, 26[7-45]; Control, 4[0-7]: p<0.01), which affected their families, particularly at nighttime. Elective-ND patients with a total respiratory symptom score >20 invariably had BAL neutrophilia. Elective patients with 16S/18S microbial rDNA positive BAL had higher neutrophil counts (positive, 33[18-70]%; negative, 8[4-38]%: p<0.05) and generally higher symptom scores (positive, 17[5-32]; negative, 5[0-9]: p = 0.097). Streptococcus mitis was commonly identified in BAL from ND children; Pseudomonas aeruginosa was not identified in any sample. Conclusions Children with severe ND often have high levels of chronic respiratory symptoms, which may relate to lower airway inflammation. Bacterial airway colonisation, particularly with oral commensals, may play a role in both symptom generation and inflammation.